Pembelajaran Kelembagaan Nasional dan Internasional untuk Penguatan Tata Kelola Lingkungan melalui Teori Bedah Jantung - Simanjuntak, Hengki; Rusdi; Sudarmanto, Arif (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2025)
The Heart Surgery Theory emerges from the ongoing governance crisis in Indonesia's environmental sector, characterized by institutional fragmentation and sectoral disconnection. This theory proposes a collaborative governance approach that emphasizes spatial and temporal synchronization combined with the application of mutual accountability across sectors. The Cantelan mechanism anchors budgetary allocations (DIPA/DPA) to specific priority locations, ensuring the simultaneous presence of forestry, environment, public works, agriculture, and social sectors in critical ecosystems. This study applies a reflective literature review combined with lessons from national and international practices, including TVA (United States), MDBA (Australia), and ICPR (Europe). The results indicate that spatial-temporal locking and mutual accountability reduce bureaucratic inefficiencies, close governance loopholes, and strengthen bureaucratic integrity in ecosystem restoration efforts.